Modeling of Asphalt Concrete Mixing Drum on Matlab® / Simulink® - T. I. Askarxodjayev; A. X. Sarmonov (Research Parks Publishing LLC, 2022)
In this article, a basic energy-intensive drum dryer was simulated using MATLAB® to improve the hot asphalt mix production process and reduce energy consumption. In this case, the results were obtained in the form of 2D and 3D plots by entering the initial data and boundary conditions. The results obtained were compared with the results obtained experimentally.